Long‐term prognostic value of dynamic function assessment of intermediate coronary lesion with computational physiology. (18th January 2022) - Guan, Changdong; Geng, Liang; Zhang, Rui; You, Jieyun; Xie, Lihua; Wang, Xingxu; Wan, Qing; Xu, Bo; Dou, Kefei; Zhang, Qi
Abstract: This study sought to investigate the dynamic functional changes of coronary intermediate lesions using quantitative flow ratio (QFR) and its implication on long‐term clinical outcomes. Physiology‐guided percutaneous coronary intervention in patients with angiographic intermediate lesions has been associated with favorable outcomes. This study consecutively enrolled 1130 patients with deferred intermediate lesions at baseline angiography and subsequently received second‐time angiography between 9 months and 2 years later from two centers in China. The functional changes of intermediate lesions at angiographic follow‐up (ΔQFR) were defined as (baseline QFR—follow‐up QFR)/years. The primary outcome was vessel‐oriented composite endpoint (VOCE), defined as the composite of vessel‐related cardiac death, vessel‐related myocardial infarction (MI), and ischemia‐driven target vessel revascularization (ID‐TVR) at angiographic follow‐up for up to 5 years. Retrospective QFR assessment was available in 820 patients (996 intermediate lesions). QFR ≤ 0.80 at second‐time angiography was associated with significantly higher 5‐year VOCE (41.9% vs. 13.4%, p < 0.0001). In 777 intermediate lesions with baseline QFR > 0.80, mean ΔQFR was 0.03 ± 0.07 (median: 0.006; Q1: 0; and Q3: 0.04). The optimal cutoff of ΔQFR for predicting the primary outcome was 0.03 (area under the curve [AUC]: 0.68). The cumulative event rate of VOCE in patients with ΔQFR ≥ 0.03 was significantly higher than in those with ΔQFR < 0.03 (33.8% vs. 12.2%, p < 0.0001), driven by higher vessel‐related MI and ID‐TVR. The ΔQFR was a useful tool for evaluating the dynamic functional change of deferred intermediate lesions, as it demonstrates good prognostic value for long‐term target vessel‐related adverse events.